Enhancement of Strength by Multiple Rolling at Room Temperature in the 1045 Steel Prepared by Aluminothermic Reaction. Issue 5 (4th January 2019) - Li, Zhengning; La, Peiqing; Ma, Jiqiang; Guo, Xin; Sheng, Jie; Shi, Yu; Zhou, Xueyuan
Abstract : The effects of cold rolling on the microstructure and mechanical properties of 1045 steel prepared by aluminothermic reaction casting method are investigated. It is found that an ultrafine‐grained ferrite ( α ) + submicron/nano‐cementite particle ( θ ) structure is formed by rolling at room temperature with different thickness reduction. With the increase of thickness reduction, many lamella cementites are squeezed, a portion of cementite is crushed, the dislocation density increases, meanwhile the tensile strength is improved significantly. The underlying mechanisms of enhancing mechanical properties are analyzed, with a focus on the heterogeneous composite structure of a soft fine‐grained matrix embedded with hard nano‐scale cementite particles. The yield strength and ultimate tensile strength are increased from 256 MPa and 490 MPa (As‐casting) to 939 MPa and 956 MPa at 84% thickness reduction. The tensile strength of rolled steel with 70% thickness reduction is 1.5 times than common 1045 carbon steel, but it also has a considerable ductility, resulting from the enhancement caused by refined ferrite grains and cementite particles. Abstract : In this paper, 1045 steel prepared by aluminothermic reaction is rolled at room temperature with different thickness reduction. With the increase of thickness reduction, the yield strength and ultimate tensile strength are increased. The tensile strength of rolled steel with 70% thickness reduction is 1.5 times than common 1045 carbon steel, but it also has a considerable ductility.